Very short answer questions : a viable alternative to multiple choice questions - Md Mizanur, Rahman; Puthiaparampil, Thomas (BMC Medical Education, 2020)
Background: Multiple choice questions, used in medical school assessments for decades, have many drawbacks such as hard to construct, allow guessing, encourage test-wiseness, promote rote learning, provide no opportunity for examinees to express ideas, and do not provide information about strengths and weakness of candidates. Directly asked, directly answered questions like Very Short Answer Questions (VSAQ) are considered a better alternative with several advantages. Objectives: This study aims to compare student performance in MCQ and VSAQ and obtain feedback. from the stakeholders. Methods: Conduct multiple true-false, one best answer, and VSAQ tests in two batches of medical students, compare their scores and psychometric indices of the tests and seek opinion from students and academics regarding these assessment methods. Results: Multiple true-false and best answer test scores showed skewed results and low psychometric performance compared to better psychometrics and more balanced student performance in VSAQ tests. The stakeholders’ opinions were significantly in favour of VSAQ. Conclusion and recommendation: This study concludes that VSAQ is a viable alternative to multiple-choice question tests, and it is widely accepted by medical students and academics in the medical faculty.